Effects of tributyltin chloride (TBTCl) antifoulingbiocide on adult males and females of brine shrimp (Artemia salina) - Mohamed Abu Shaala, Najla; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad; Azmai, Mohammed Noor Amal; Mohamat Yusuff, Ferdaus; Omar, Hishamuddin (Science Publishing Corporation, 2017)
Elevation of tributyltin (TBT) concentration in marine environment could affect targeted and non-targeted organisms at any lifestage. The present study aimed to determine median lethal concentration (LC50) and morphological effects of tributyltin chloride (TBTCl) on adult males and females of brine shrimp (Artemia salina). The adult males and females of A. salina were exposed to different concentration of TBTCl. Morphological condition of every A. salina individuals were observed under a microscope. Results showed the LC50 of TBTCl among adult males of A. salina was 146.99 ng.L-1 and for the females was 94.72 ng.L-1, respectively. The LC50 of TBTCl was significantly different among different sexes. There was also a significant difference in some morphological characters of males and females exposed to different TBTCl concentrations. These morphological changes include their total length, head width, abdominal width, and tail width after the 24hr exposure to TBTCl. These results suggested that suspensions of the TBTCl were toxic to Artemia, most likely due to the formation of benign TBTCl aggregates in water. However, the mortality increased with extended exposure to 24hr. Highest mortality occurred at 200 ng.L-1 TBTCl; 43.33% for male and 90% for female (LC50<150 ng.L-1) for both. Depended on this the female was more sensitive for TBTCl toxicity test when compared to male. These effects were attributed to changes in morphological characteristics of the body A. salina.